Cognitive computing and big data analytics - Hurwitz, Judith; Kaufman, Marcia; Bowles, Adrian, 1952- (Hoboken : John Wiley & Sons, 2015)
This book provides detailed guidance toward building a new class of systems that learn from experience and derive insights to unlock the value of big data. It helps technologists understand cognitive computing's underlying technologies, from knowledge representation techniques and natural language processing algorithms to dynamic learning approaches based on accumulated evidence, rather than reprogramming. Case examples from financial, healthcare, and manufacturing walk readers through the design and testing of cognitive systems. Topics include: how cognitive computing evolved from promise to reality; elements of a cognitive computing system; hardware and software technologies behind cognitive computing; evaluation of your own application portfolio; cognitive computing capabilities to transform the organization. --
The Foundation of Cognitive Computing -- Design Principles for Cognitive Systems -- Natural Language Processing in Support of a Cognitive System -- The Relationship Between Big Data and Cognitive Computing -- Representing Knowledge in Taxonomies and Ontologies -- Applying Advanced Analytics to Cognitive Computing -- The Role of Cloud and Distributed Computing in Cognitive Computing -- The Business Implications of Cognitive Computing -- IBM's Watson as a Cognitive System -- The Process of Building a Cognitive Application -- Building a Cognitive Healthcare Application -- Smarter Cities: Cognitive Computing in Government -- Emerging Cognitive Computing Areas -- Future Applications for Cognitive Computing.
Includes index.
CIP data; item not viewed.
Keywords: Expert systems (Computer science); Big data; Artificial intelligence; Electronic books